Sex determination in honeybees: two separate mechanisms induce and maintain the female pathway. - Tanja Gempe (Public Library of Science (PLoS), 2009)
Organisms have evolved a bewildering diversity of mechanisms to generate the two sexes. The honeybee (Apis mellifera) employs an interesting system in which sex is determined by heterozygosity at a single locus (the Sex Determination Locus) harbouring the complementary sex determiner (csd) gene. Bees heterozygous at Sex Determination Locus are females, whereas bees homozygous or hemizygous are males. Little is known, however, about the regulation that links sex determination to sexual differentiation. To investigate the control of sexual development in honeybees, we analyzed the functions and the regulatory interactions of genes involved in the sex determination pathway. We show that heterozygous csd is only required to induce the female pathway, while the feminizer (fem) gene maintains this decision throughout development. By RNAi induced knockdown we show that the fem gene is essential for entire female development and that the csd gene exclusively processes the heterozygous state. Fem activity is also required to maintain the female determined pathway throughout development, which we show by mosaic structures in fem-repressed intersexuals. We use expression of Fem protein in males to demonstrate that the female maintenance mechanism is controlled by a positive feedback splicing loop in which Fem proteins mediate their own synthesis by directing female fem mRNA splicing. The csd gene is only necessary to induce this positive feedback loop in early embryogenesis by directing splicing of fem mRNAs. Finally, fem also controls the splicing of Am-doublesex transcripts encoding conserved male- and female-specific transcription factors involved in sexual differentiation. Our findings reveal how the sex determination process is realized in honeybees differing from Drosophila melanogaster.